Pengaruh Pelayanan Terhadap Kepuasan Pengunjung di Wisata Taman Anggrek Kota Surabaya - Erny Kusumawati; Indah Murti; Dida Rahmadanik (Faculty of Social and Political Science, 2022)
Improving the quality of public services is one of the most important things in public services. As a public service provider, the government must carry out its full responsibility and continue to strive to provide the best service to improve the quality of public services. The level of service quality is defined as satisfactory and good, and if the level of service quality provided exceeds the picture expected by the community, it is considered ideal. This study uses quantitative methods. The location used as a place to conduct this research is the Surabaya City Orchid Garden. The sample in this study were visitors to the Surabaya City Orchid Garden 2021 as many as 100 respondents using the Purposive Random Sampling method. The analysis technique used in this research is simple linear regression analysis. The results of the analysis in this study provide the fact that the service has a significant and positive effect on visitor satisfaction at the Surabaya Orchid Garden. This means that when the service provided is perceived as good by the community, it will have an impact on higher community satisfaction. So that this can be a reference for the Surabaya City Cleanliness and Green Open Space Service (DKRTH) to be able to increase the satisfaction of the people who visit the Surabaya City Orchid Park Tour to be better in providing services to the community. The conclusion obtained in this study is that the service has a significant and positive effect on visitor satisfaction at Taman Anggrek Surabaya City which refers to the Tangible, Reliability, Responsiveness, Assurance, and Empathy dimensions which have a good level which has an impact on increasing community satisfaction.